A comparative study on research exemptions in plant breeding under intellectual property rights protection. Issue 1 (February 2016) - Hsu, Shun-Liang
Abstract : The protection of plants through the patent system and through a sui generis system of plant variety protection causes numerous difficulties and tensions when the protection granted overlaps and intersects. This article explores the particular difficulties that arise in relation to plant research. It considers and contrasts the scope of the research exception as it applies to intellectual property rights (IPR) and the difficulties caused by the divergences in scope.